Asymmetric visual capture of virtual sound sources in the distance dimension - Zahorik, Pavel (Frontiers in Neuroscience, 2022)
Visual capture describes the tendency of a sound to be mislocalized to the location of a plausible visual target. This effect, also known as the ventriloquist effect, has been extensively studied in humans, but primarily for mismatches in the angular direction between auditory and visual targets. Here, visual capture was examined in the distance dimension using a single visual target (an un-energized loudspeaker) and invisible virtual sound sources presented over headphones. The sound sources were synthesized from binaural impulse-response measurements at distances ranging from 1 to 5 m (0.25 m steps) in the semi-reverberant room (7.7 × 4.2 × 2.7 m3) in which the experiment was conducted. Listeners (n = 11) were asked whether or not the auditory target appeared to be at the same distance as the visual target. Within a block of trials, the visual target was placed at a fixed distance of 1.5, 3, or 4.5 m, and the auditory target varied randomly from trial-to-trial over the sample of measurement distances. The resulting psychometric functions were generally consistent with visual capture in distance, but the capture was asymmetric: Sound sources behind the visual target were more strongly captured than sources in front of the visual target. This asymmetry is consistent with previous reports in the literature, and is shown here to be well predicted by a simple model of sensory integration and decision in which perceived auditory space is compressed logarithmically in distance and has lower resolution than perceived visual space.